Implications of platform finance on monetary policy transmission - Chin-Yoong Wong; Yoke-Kee Eng (Asian Development Bank Institute (ADBI), 2019)
The emergence of a decentralized peer-to-peer platform that matches lending and borrowing without collateral requirements has called the bank lending and balance-sheet channels for monetary transmission into question. Via a standard New Keynesian macroeconomic model expanded with two-sided platform and group identity, we put forward a novel platform density channel of monetary transmission, which could overshadow the conventional channels. An increase in policy rate, for instance, would instigate a shift toward platform borrowing. Increasing borrowers' density attracts participation in platform deposits, which in turn further enhances borrowers' benefit of joining the platform, making liquidity available at decreasing platform loan rates. Business investment and hence the inflation rate gets lifted despite monetary tightening. The implication of a platform density channel diminishes, however, when platform borrowings pose nontrivial risk of default.
Keywords: E43; E44; E52; 330; P2P lending; digital finance; two-sided platform; group identity; monetary transmission